Acute effects of sodium bicarbonate ingestion on cycling time-trial performance: A systematic review and meta-analysis of randomized controlled trials - Lopes-Silva, J. P.; Correia-Oliveira, C. R. (European Journal of Sport Science, 2023)
This study aimed to investigate the isolated effects of NaHCO3 on cycling time-trial performance. Furthermore, we investigated whether the ingestion time of NaHCO3, standardized or individualized based on time to peak, could be effective in improving cycling time-trial performance. A systematic review was carried out on randomized placebo-controlled studies. A random-effects meta-analysis assessed the standardized mean difference (SMD) between NaHCO3 and placebo conditions. Eighteen studies were qualitatively (systematic review) and quantitatively (meta-analysis) analysed concerning mean power output (Wmean) (n = 182) and time performance (n = 201). The reviewed studies showed a low risk of bias and homogenous results for Wmean (I2 = 0%) and performance time (I2 = 0%). Overall, when compared to placebo, the NaHCO3 ingestion improved the Wmean (SMD: 0.42; 95% CI: 0.21-0.63; P = 0.001) and performance time (SMD: 0.22; 95% CI: 0.02-0.43; P = 0.03). Similarly, the NaHCO3 ingestion using a time-to-peak strategy improved the Wmean (SMD: 0.39; 95% CI: 0.03-0.75; P = 0.04; I2 = 15%) and performance time (SMD: 0.34; 95% CI: 0.07-0.61, P = 0.01, I2 = 0%). The present findings reveal that NaHCO3 ingestion has the potential to increase the overall performance time and Wmean in cycling time trials.